Growth Performance of Indian Major Carps at Pond System Using Shrimp Industry Waste in their Diet - Hossain, MI; Shikha, FH; Hoque, ABMA (Journal of Environmental Science and Natural Resources, 2021)
A study was carried out to observe the growth performance of Indian major carp utilizing the shrimp industry waste in their supplementary diets in pond system during 1st January to 30th June, 2015. Two types of diet namely Diet-1 (Formulated feed with shrimp waste), Diet-2 (Formulated feed with plants source ingredients) were prepared while Diet-3 (Commercial feed) were purchased from the market and assigned to three treatments viz. T1, T2 and T3. Protein percentage of diets were 28.42%, 28.13% and 27.32%, respectively. The water quality parameters of the experimental ponds were monitored at 10 days interval. Diet-1 resulted better growth with Labeo rohita (153.68g), Gibelion catla (170.14g) and Cirrhinus cirrhosus (84.83g) compared to Diet-2 (138.99g, 152.94g, 68.39g respectively). The highest SGR (%/day) value was obtained with Labeo rohita (2.66%/day), Gibelion catla (2.59%/day) and Cirrhinus cirrhosus (2.62%/day) for Diet-3. The average protein efficiency ratio (PER) for Diet-1 (2.19) differed much to that of Diet-2 (2.03) where Diet-3 (2.38) showed highest PER value. The highest survival rate (%) with Labeorohita (93.93%), Gibelioncatla (92.86%) Cirrhinuscirrhosus (94.44%) were found for Diet-3. Therefore, it could be recommended that shrimp industry waste can be replaced with fish meal in the diets of Indian major carps along with other available feed ingredients. Environ. Sci. & Natural Resources, 12(1&2): 101-108, 2019